BENEFITS AND ATTITUDES OF INDONESIAN UNIVERSITY STUDENTS TOWARDS EXTENSIVE READING ACTIVITIES IN LEARNING ENGLISH GRAMMAR - Maryani, Maryani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
In learning a second or foreign language, students commonly read for pleasure, which is called extensive reading (ER). Extensive reading is commonly related to increasing vocabulary knowledge and reading skills; however, extensive reading can also expand learners’ grammatical knowledge Based on the study of Khansir and Dehghani (2015), it was found that ER has improved their Iranian participants’ English grammar (as stated in Ng, Renandya, Chong, 2019, p. 180-181). Referring to the positive outcome of their study, this study aims to investigate Indonesian university students’ perceptions of the benefits of ER activities on their English grammar knowledge and also their attitudes after experiencing ER activities in Grammar class. The research participants were 30 Indonesian university students who attended Grammar classes at a private university in West Java. The instruments used were an online questionnaire which was distributed at the end of the semester and the students’ weekly ER log. The questionnaire result was counted manually before they were classified into certain categories, whereas content analysis was used to select and analyze the data from the learning log. The findings show both positive and negative outcomes regarding the students’ grammar knowledge and attitudes.